A Comparison of Spinal Anesthesia Versus Monitored Anesthesia Care With Local Anesthesia in Minimally Invasive Fetal Surgery. (February 2020) - Ferschl, Marla B.; Feiner, John; Vu, Lan; Smith, Devon; Rollins, Mark D.
Abstract : BACKGROUND: Minimally invasive fetal surgery is commonly performed to treat twin-to-twin transfusion syndrome with selective fetoscopic laser photocoagulation and twin-reversed arterial perfusion sequence using radiofrequency ablation. Although an increasing number of centers worldwide are performing these procedures, anesthetic management varies. Both neuraxial anesthesia and monitored anesthesia care with local anesthesia are used at different institutions. We sought to determine the efficacy and outcomes of these 2 anesthetic techniques for fetal procedures at our institution. METHODS: All patients undergoing minimally invasive fetal surgery for twin-to-twin transfusion syndrome or twin-reversed arterial perfusion sequence over a 6-year time period (2011–2016) were reviewed. Patients receiving monitored anesthesia care with local anesthesia were compared with those receiving spinal anesthesia in both selective fetoscopic laser photocoagulation and radiofrequency ablation fetal procedures. The primary outcome examined between the monitored anesthesia care and spinal anesthesia groups was the difference in conversion to general anesthesia using a noninferiority design with a noninferiority margin of 5%. Secondary outcome measures included use of vasopressors, procedure times, intraoperative fluids administered, maternal complications, and unexpected fetal demise within 24 hours of surgery. RESULTS: The difference in failure rate between monitored anesthesia care and spinal was −0.5% (95% CI, −4.8% to 3.7%). Patients receiving monitored anesthesia care plus local anesthesia were significantly less likely to need vasopressors, had a shorter presurgical operating room time, and received less fluid ( P < .001). Operative time did not differ significantly. CONCLUSIONS: Monitored anesthesia care plus local anesthesia is a reliable and safe anesthetic choice for minimally invasive fetal surgery. Furthermore, it decreases maternal hemodynamic instability and reduces preincision operating room time.